Fighting Fire With Fires: The Fire‐Fuel Feedback Effect in Canadian Forests - Weiwei Wang; Xianli Wang; Tom Swystun; Tongli Wang; Jacqueline A. Oliver; Mike D. Flannigan; Wanli Wu; John L. Innes; Guangyu Wang (Global Ecology and Biogeography, 2026)
Aim Climate‐driven fire increases could be modified by fire‐fuel feedback, as recent fires reduce burnable fuels for future fires. Knowing the effects of fire‐fuel feedback is essential for more accurate projection of fire activity, which, however, has often been overlooked due to the challenge in its quantification. This study aims to project future fire activity under the changing climates with consideration for fire‐fuel feedback effects across Canada. Location Canadian forests. Time Period 1981–2100. Major Taxa Studied Trees. Methods We projected future changes in a full set of fire activity variables, including annual area burned (AAB), annual number of fires (ANF) and annual maximum fire size (MFS), based on extreme fire weather in Canada. We then incorporated fire‐fuel feedback into the projections to quantify its effects in Canadian forests and consequently answered the question of whether the unprecedented 2023 fire season would become a common occurrence in the future. Results The feedback from fires within 6–11 years prior showed the strongest power in rectifying fire activity projections, and the feedback effects strengthened as climate change became more severe. By century's end (2080s), under the extreme climate change scenario (RCP8.5), fire‐fuel feedback could reduce weather‐based AAB, ANF and MFS projections by 21%, 21% and 16%, respectively. Spatially, eastern and northwestern regions may see the greatest fire activity increases, while the strongest feedback effects appear in the south and northwest. In the 2080s, under RCP8.5, years with more extensive fires than 2023 may occur once every 9 years in regions most affected by the unprecedented 2023 fire season. Main Conclusions The results indicate that fire‐fuel feedback could modestly mitigate climate‐driven increases in future fire activity in Canadian forests. With more accurate projections that account for such feedback effects, the extraordinary 2023 fire season could be considered a low‐frequency but more plausible occurrence in the future.

Integrating bamboo forests into the carbon markets: Insights from China - Chunyu Pan; Anil Shrestha; Chong Li; Mengjia Ying; Jie Duan; Mei He; Weirong Zhu; Qinghui Chai; John L. Innes; Robert Kozak; Guomo Zhou; Guangyu Wang (Journal of Environmental Management, 2025)

DNA metabarcoding of stomach contents shows predation impacts of black rats on island birds after a resource pulse are driven by numerical not functional response - Joanna K. Carpenter; Alexander J. F. Verry; Kieren J. Mitchell; Katherine Trought; Adrian Monks; John Innes; James Griffiths; Max Harvey; Janet M. Wilmshurst (Biological Invasions, 2025)
Generalist predator populations often surge during resource pulses but decline sharply afterwards and shift to alternative prey sources, which experience elevated predation rates. Understanding these numerical and functional responses of predators to resource pulses is especially important for effectively managing island ecosystems, where invasive mammals are generalist predators and vulnerable indigenous birds are alternative prey. We used DNA metabarcoding of stomach contents to test whether the proportion of black rats ( Rattus rattus ) consuming birds changed during and after a mast seeding year in a New Zealand beech forest. Contrary to prevailing assumptions that black rats in forests consume birds only occasionally and increase their consumption of birds once a resource pulse finishes, we found that the overall proportion of rats consuming birds was surprisingly high (19.4%), and that the proportion of rats consuming birds did not change significantly across the three years of a beech mast cycle. We detected 15 unique bird taxa in the rat stomachs and 40 unique plant taxa. The frequency of beech consumption declined across the three years, as predicted. We conclude that (1) forest birds are a common part of rat diet rather than an occasional opportunistic prey item, and (2) the impact of black rats on indigenous birds following seed pulses is predominantly driven by the numerical response (increased numbers of rats present) rather than a functional (prey switching) response. Conservation interventions that seek to maximally and consistently suppress rats are therefore likely to have the best outcomes for birds.

Survive, revive, and thrive: The impact of COVID-19 on global park visitation - Dehui Christina Geng; John L. Innes; Guangyu Wang (Science of The Total Environment, 2024)

Testing the thermal squeeze hypothesis: Do temperature and invasive species determine vital rates of New Zealand's forest birds? - Ann-Kathrin V. Schlesselmann; John Innes; Susan Walker; Neil Fitzgerald; Graeme Elliott; Adrian Monks (Biological Conservation, 2024)

Conservation of skinks in New Zealand cities - Christopher K. Woolley; Stephen Hartley; John G. Innes; Danielle F. Shanahan; Yolanda van Heezik; Deborah J. Wilson; Nicola J. Nelson (Urban Ecosystems, 2023)
Urbanisation dramatically alters ecosystems, disrupting key processes and threatening species persistence. Despite growing knowledge of the impacts of cities on wildlife, particularly for birds and mammals, there remains a paucity of research on how urbanisation impacts other taxa, including reptiles. We examined how urbanisation affects skink communities across multiple New Zealand cities by undertaking pitfall trapping surveys in a range of habitats. Of the 20 endemic species thought to have been present historically in the cities, only four were captured during surveys, Oligosoma aeneum in Hamilton; O. polychroma , O. aeneum , and O. ornatum in Wellington; O. polychroma in Nelson; and O. aff. polychroma Clade 5 in Dunedin. Our results reveal highly variable patterns of occupancy, abundance, and complex associations with key threats and habitat modifications. Sites in Nelson and Wellington were much more likely to record skinks than Hamilton and Dunedin, and modelling showed abundance of O. polychroma was positively related to rat tracking rates when grass cover was low but showed a negative relationship when grass cover was high. O. polychroma body condition was negatively associated with the proportion of urban land cover (built up areas or transport infrastructure). The low number of captures of several species is concerning and long-term monitoring is needed to assess the trajectories of these vulnerable populations. Effective conservation management of urban wildlife requires knowledge of where populations exist and how urban processes affect persistence. For understudied urban-dwelling taxa such as reptiles, the lack of this information may be putting populations at risk.

Pushing the limits: ship rat (Rattus rattus) population dynamics across an elevational gradient in response to mast seeding and supplementary feeding - Joanna K. Carpenter; Adrian Monks; John Innes; James Griffiths (Biological Invasions, 2022)
Understanding marginal habitat use by invasive species is important for predicting how distributions may change under future climates. We investigated the influence of food availability and temperature on ship rat ( Rattus rattus ) distribution and density across a forested elevational gradient in New Zealand by measuring ship rat demographics following a beech (Nothofagaceae) mass seeding event (‘mast’) at three elevation bands (20–80, 400–500, 800–900 m asl). We tested whether declining food availability limits rat populations at the highest elevation band post-mast by experimentally increasing food abundance above baseline food availability. When our study started 4 months post-seedfall, rats at mid- and low- elevations were at high densities (11.4–16.5 ha −1 ). Rats at higher elevations were barely detectable, but densities peaked (9.4 ha −1 ) 10 months post-seedfall, with the initial increase possibly driven by immigration from lower elevations. All populations declined sharply over the next year. Supplementary feeding at high elevation increased survival, recruitment, and density of rats through winter, 16 months post-seedfall, relative to unfed grids, suggesting food limitation. However, both fed and non-fed populations declined to zero by the following spring, perhaps due to stoat ( Mustela erminea ) predation. Our results suggest that low food availability plays a significant role in restricting rats from cool, high elevation environments. The variation in the timing and magnitude of ship rat responses to the pulsed resource across the gradient also highlights the importance of initial population size and spatial processes as factors modulating ship rat responses to pulsed resources across a landscape.

Invasive species and thermal squeeze: distribution of two invasive predators and drivers of ship rat (Rattus rattus) invasion in mid-elevation Fuscospora forest - Holly A. L. Harris; Dave Kelly; John Innes; Robert B. Allen (Biological Invasions, 2022)
Global climate change could alter the range, abundance, and interactions of species, potentially favouring invasive species and harming endemics. Ship rats ( Rattus rattus ) are one of the world's worst invasive predators but are typically absent from Aotearoa New Zealand's native Fuscospora cliffortioides (mountain beech) forest above 1000 m. Stoats ( Mustela erminea ) are another damaging invasive predator in Aotearoa New Zealand and prey on ship rats. We analyse community trapping records 2007–2020 to investigate the spatial and temporal distribution of ship rats and their key predator stoats at Craigieburn Forest Park. We document an invasion of ship rats after 2010 at Craigieburn and hypothesised two drivers of the increase in rat abundance: (1) more frequent mountain beech high-seed years providing more food for rats; and (2) warming winter temperatures allowing rats to invade areas that were previously too cold. We were unable to test a third possible driver (stoat trapping resulting in top-down meso-predator release) due to the nature of the data available. Rats were more common at low altitudes near streams, and stoats were more common at higher-altitudes on forest edges. Average winter temperature, but not seedfall, increased significantly at Craigieburn mid-elevations since 1972. The best predictor of annual rat catch was higher average winter temperatures interacting with high seedfall. This shows a key interaction between two global change drivers: warming temperatures have allowed exotic ship rats to expand into areas where they were previously absent, increasing the resultant "thermal squeeze" of predation on sensitive endemic birds at higher-altitude sites.

Tree Vitality and Forest Health: Can Tree-Ring Stable Isotopes Be Used as Indicators? - Paolo Cherubini; Giovanna Battipaglia; John L. Innes (Current Forestry Reports, 2021)
Purpose of Review Society is concerned about the long-term condition of the forests. Although a clear definition of forest health is still missing, to evaluate forest health, monitoring efforts in the past 40 years have concentrated on the assessment of tree vitality, trying to estimate tree photosynthesis rates and productivity. Used in monitoring forest decline in Central Europe since the 1980s, crown foliage transparency has been commonly believed to be the best indicator of tree condition in relation to air pollution, although annual variations appear more closely related to water stress. Although crown transparency is not a good indicator of tree photosynthesis rates, defoliation is still one of the most used indicators of tree vitality. Tree rings have been often used as indicators of past productivity. However, long-term tree growth trends are difficult to interpret because of sampling bias, and ring width patterns do not provide any information about tree physiological processes. Recent Findings In the past two decades, tree-ring stable isotopes have been used not only to reconstruct the impact of past climatic events, such as drought, but also in the study of forest decline induced by air pollution episodes, and other natural disturbances and environmental stress, such as pest outbreaks and wildfires. They have proven to be useful tools for understanding physiological processes and tree response to such stress factors. Summary Tree-ring stable isotopes integrate crown transpiration rates and photosynthesis rates and may enhance our understanding of tree vitality. They are promising indicators of tree vitality. We call for the use of tree-ring stable isotopes in future monitoring programmes.

Excluding mammalian predators increases bird densities and seed dispersal in fenced ecosanctuaries - Sara P. Bombaci; John Innes; Dave Kelly; Victoria Flaherty; Liba Pejchar (Ecology, 2021)
Islands are epicenters of animal extinctions and population declines. These losses exacerbate biodiversity loss and disrupt ecological services in areas of high endemism. Island defaunation is primarily driven by invasive mammalian predators, and mammal eradications are reversing population declines for some island species. Invasive mammal eradications may also have the capacity to restore ecological interactions, along with the recovery of island fauna. Here we show that invasive mammal eradication in fenced ecosanctuaries results in higher rates of bird foraging on fruit, and higher bird‐mediated seed dispersal, than in similar forests without mammal eradication. We further show that higher foraging and seed dispersal is related to higher densities of native bird species, after accounting for natural variation in fruit availability. For the many other systems globally that are under threat from invasive mammals, New Zealand’s fenced ecosanctuary model offers a promising tool for restoring biodiversity and ecosystem services.

What was the ecological impact of a Trypillia megasite occupation? Multi-proxy palaeo-environmental investigations at Nebelivka, Ukraine - Bruce Albert; Jim Innes; Konstantin Krementskiy; Andrew R Millard; Bisserka Gaydarska; Marco Nebbia; John Chapman (Vegetation History and Archaeobotany, 2020)

Spatial patterns and drivers of invasive rodent dynamics in New Zealand forests - Susan Walker; Joshua R. Kemp; Graeme P. Elliott; Corey C. Mosen; John G. Innes (Biological Invasions, 2019)

Quantitative Holocene climatic reconstructions for the lower Yangtze region of China - Jianyong Li; John Dodson; Hong Yan; Weiming Wang; James B. Innes; Yongqiang Zong; Xiaojian Zhang; Qinghai Xu; Jian Ni; Fengyan Lu (Climate Dynamics, 2018)

Evaluating tree wētā (Orthoptera: Anostostomatidae: Hemideina species) as bioindicators for New Zealand national biodiversity monitoring - Corinne Watts; Ian Stringer; John Innes; Joanne M. Monks (Journal of Insect Conservation, 2017)

Multiple factors influence plant richness and diversity in the cold and dry boreal forest of southwest Yukon, Canada - Shyam K. Paudel; Patrick O. Waeber; Suzanne W. Simard; John L. Innes; Craig R. Nitschke (Plant Ecology, 2016)

Traits influencing range contraction in New Zealand’s endemic forest birds - Elizabeth H. Parlato; Doug P. Armstrong; John G. Innes (Oecologia, 2015)

Potential effect of climate change on observed fire regimes in the Cordilleran forests of South-Central Interior, British Columbia - Craig R. Nitschke; John L. Innes (Climatic Change, 2013)

Unstable climate−growth relations for white spruce in southwest Yukon, Canada - Raphaël D. Chavardès; Lori D. Daniels; Patrick O. Waeber; John L. Innes; Craig R. Nitschke (Climatic Change, 2013)

National Park Development in China: Conservation or Commercialization? - Guangyu Wang; John L. Innes; Sara W. Wu; Judi Krzyzanowski; Yongyuan Yin; Shuanyou Dai; Xiaoping Zhang; Sihui Liu (Ambio, 2012)

Framework for assessing the impact of human activities on the environment: the impact of forest harvesting and petroleum drilling on habitat of moose (Alces alces) and marten (Martens americana) - Bogdan M. Strimbu; John L. Innes (Biodiversity and Conservation, 2012)

Reinvasion by ship rats (Rattus rattus) of forest fragments after eradication - Carolyn M. King; John G. Innes; Dianne Gleeson; Neil Fitzgerald; Tom Winstanley; Barry O’Brien; Lucy Bridgman; Neil Cox (Biological Invasions, 2011)

A deterministic harvest scheduler using perfect bin-packing theorem - Bogdan M. Strimbu; John L. Innes; Victor F. Strimbu (European Journal of Forest Research, 2010)

On the Use of Statistical Tests with Non-Normally Distributed Data in Landscape Change Detection - Bogdan Strimbu; Gordon Hickey; Vladimir Strimbu; John Innes (Forest Science, 2009)
Research assessing changes of the main attributes describing forested landscapes often supply contradictory findings when viewed within an unchanging socioeconomic framework (i.e., unchanging forest management policies and no human population increase). Some studies suggest forest decline, others no change, and others expansion. We used ground-measured forest inventory data from Romania to examine the evolution of the forested landscape over a 10-year period (1993–2003), during which no substantial transformations occurred in the human population or in forest management policies. Within a repeated-measures framework, a range of parametric and nonparametric statistical tests were used to evaluate forest change. Our results revealed that significant structural changes occurred at the landscape level. The changes were detected by several multivariate and nonparametric techniques. Multivariate techniques revealed that “age class,” “phyto-climatic zone,” and “ownership type” attributes had a significant influence in delineating between the 1993 and 2003 forested landscape. The univariate nonparametric tests indicated that there are factors not considered in the planning process (such as ownership or inflation) that can lead to a significant decrease of the main quantitative forest attributes (such as canopy closure or height), a decrease undetected by the corresponding parametrical statistics. Our research revealed that even when the distribution did not exhibit significant skewness, the nonparametric techniques could be more efficient than the corresponding parametric techniques by detecting significant changes of the attributes describing the forested landscape.

Climatic change and fire potential in South‐Central British Columbia, Canada - CRAIG R. NITSCHKE; JOHN L. INNES (Global Change Biology, 2008)
The incidence and severity of forest fires are linked to the interaction between climate, fuel and topography. Increased warming and drying in the future is expected to have a significant impact on the risk of forest fire occurrence. An increase in fire risk is linked to the synchronous relationship between climate and fuel moisture conditions. A warmer, drier climate will lead to drier forest fuels that will in turn increase the chance of successful fire ignition and propagation. This interaction will increase the severity of fire weather, which, in turn, will increase the risk of extreme fire behaviour. A warmer climate will also extend fire season length, which will increase the likelihood of fires occurring over a greater proportion of the year. In this study of the North Okanagan area of British Columbia, Canada, the impacts of climate change of fire potential were evaluated using the Canadian Forest Fire Danger Rating System and multiple climate scenario analysis. Utilizing this approach, a 30% increase in fire season length was modelled to occur by 2070. In addition, statistically significant increases in fire severity and fire behaviour were also modelled. Fire weather severity was predicted to increase by 95% during the summer months by 2070 while fire behaviour was predicted to shift from surface fire‐intermittent crown fire regimes to a predominantly intermittent‐full crown fire regime by 2070 onwards. An increase in fire season length, fire weather severity and fire behaviour will increase the costs of fire suppression and the risk of property and resource loss while limiting human‐use within vulnerable forest landscapes. An increase in fire weather severity and fire behaviour over a greater proportion of the season will increase the risks faced by ecosystems and biodiversity to climatic change and increase the costs and difficulty of achieving sustainable forest management.

Evidence of Elevated Ozone Concentrations on Forested Slopes of the Lower Fraser Valley, British Columbia, Canada - Judi Krzyzanowski; Ian G. McKendry; John L. Innes (Water, Air, & Soil Pollution, 2006)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.

Monitoring Sustainable Forest Management in Different Jurisdictions - Gordon M. Hickey; John L. Innes (Environmental Monitoring and Assessment, 2005)

Dog MHC alleles containing the human RA shared epitope confer susceptibility to canine rheumatoid arthritis - William Ollier; Lorna Kennedy; Wendy Thomson; Annette Barnes; Susan Bell; David Bennett; John Angles; John Innes; Stuart Carter (Immunogenetics, 2001)

Why Economics Matters for Endangered Species Protection - Jason F. Shogren; John Tschirhart; Terry Anderson; Amy Whritenour Ando; Steven R. Beissinger; David Brookshire; Gardner M. Brown; Don Coursey; Robert Innes; Stephen M. Meyer; Stephan Polasky (Conservation Biology, 1999)
We offer three reasons why economics matters more to species protection than many people think and what this implies for the ongoing debate over the reauthorization of the Endangered Species Act of 1973. Economics matters because (1) human behavior generally, and economic parameters in particular, help determine the degree of risk to a species; (2) in a world of scarce resources, the opportunity cost of species protection—the costs of reduced resources for other worthwhile causes—must be taken into account in decision making; and (3) economic incentives are critical in shaping human behavior, and consequently the recovery of species. Endangered species protection that explicitly addresses these basic principles can avoid wasting valuable resources that yield no gain in species protection.

Forest biodiversity and its assessment by remote sensing - JOHN L. INNES; BARBARA KOCH (Global Ecology and Biogeography, 1998)